Phenotypic Reversion of Somaclonal Variants Derived from Inflorescence of Date Palm (Phoenix dactylifera L.) in the Open Field Trials - Mirani, Abdul Aziz; Teo, Chee How; Abul-Soad, Adel Ahmed; Markhand, Ghulam S.; Jatt, Tahira; Mirbahar, Ameer A.; Solangi, Najamuddin (Smith and Franklin Academic Publishing, 2019)
The likelihood and degree of the reversion of somaclonal variations have not been reported for tissue-cultured date palm (Phoenix dactylifera) plants derived from immature inflorescences. In this study, three to four years old field grown tissue cultured date palm plants of cvs. Kashuwari and Gulistan derived from in vitro subculture 1-10 (block I) and 11-25 (block II) in multiplication stage were screened for type and nature of phenotypic abnormalities. Six phenotypic abnormalities were detected: 1) dwarfism, 2) excessive vegetative growth, 3) production of deformed offshoots and twisted inflorescence, 4) abnormal frond growth, 5) low levels of fruit setting and 6) inflorescence absent. Among the six different variant phenotypes, complete reversion of phenotypic abnormalities for the phenotypes of inflorescence absent, low level of fruit setting, production of deformed offshoots, and abnormal frond growth were observed in open field trial plants during the three years' study period. An overall percentage of all the variations was higher (64.19%) in block II during the first season as compared to block I (2.42%). This study provides a good indicator for the date palm tissue culture industry where in vitro cultures with subculture number <11 cycles in multiplication stage are needed to obtain higher percentage of true-to-type regenerants. © 2019, Researchers Links Ltd.